STIGMA PATIENT LEADER IN SUMBERARUM VILLAGE DISTRICT DANDER DISTRICT BOJONEGORO YEAR 2017 - Septiawan, Lucky Ferry; MULYANI, SRI; Susanti, Dwi Agun (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2018)
The stigma of some diseases and disorders is a central issue in public health. Public health practitioners begin to be interested and conduct research related to the stigma of a disease before taking a health policy that will be implemented in overcoming the problem. Leprosy or leprosy (also called hansen morbus) is a chronic infectious disease caused by mycobacterium leprae bacteria. The purpose of this study identified the stigma of leprosy patients in Sumberarum Village dander Bojonegoro District.The type of this research is descriptive research. The population is all lepers in Sumberarum Village, Dander District Bojonegoro Regency, 42 respondents, with 42 respondents who meet the inclusion criteria by using non probability sampling with total sampling technique. How to collect data with questionnaires which then in editing, coding, scoring and tabulating, disajijkan in the table of estimation curve and percentage.The results showed that from 44 respondents most experienced Internalized stigma that is as much as 33 people (75%) and some respondents experienced Fell stigma that is as many as 11 people (25%).In conclusion, most of the stigma of leprosy in Sumberarum Village, Dander Sub-district of Bojonegoro is Internalized stigma. It is hoped as an input to the community that leprosy can be cured with regular treatment, and must build a positive attitude that the disease can be cured.